Study of onychomycosis - Nayak, Sarita Kumari; Krishna, P. Bala Murali; Lakshmi, N. (International Journal of Research in Medical Sciences, 2020)
Background: Onychomycosis is one of the most common fungal nail infections caused by Dermatophytes, Non-Dermatophytic Molds (NDM) and Yeast. Though it is not life-threatening, can cause pain, discomfort, and disfigurement. It decreases the nail growth rate. Objectives: This study was carried out to document the clinico-mycological pattern and antifungal susceptibility pattern of onychomycosis. Methods: The study group included 130 consecutive patients with suspected fungal nail infections, attending Dermatology outpatient department of King George Hospital, Visakhapatnam, Andhra Pradesh during November 2012 to August 2014. The nail clippings of the patients were collected and subjected to KOH mounts for direct microscopy and fungal culture and antifungal susceptibility tests. Results: Onychomycosis was common among males (66.92%) than females (33.08%) with highest incidence was in age group 31-40 years (41.37%). Finger or toenails were exclusively involved in 32.18% and 55.18% patients respectively while these were involved concurrently in the rest of the 12.65% patients. Distal and lateral subungual onychomycosis seen in 64.36% of the patients was the most common clinical type. KOH and culture positivity were recorded in 56.92% and 48.46% cases respectively. Dermatophytes (50.58%) were predominant isolate followed by NDM (27.58%) and yeast (21.84%). Clotrimazole and ketoconazole were most effective antifungals against dermatophytes. For NDM, itraconazole, nystatin and amphotericin B and for yeast fluconazole and itraconazole were effective. Conclusions: The present study gives an insight about the aetiological agents causing onychomycosis and their anti-fungal susceptibility pattern in this region. Thus, it can help in taking adequate control measures to prevent it.